(untitled) (European Journal of Pure and Applied Mathematics, 2021)
Let G = (V, E) be a graph of order 2n. If A ⊆ V and hAi ∼= hV , then A is said to be isospectral. If for every n-element subset A of V we have hAi ∼= hV , then we say that G is spectral-equipartite. In [1], Igor Shparlinski communicated with Bibak et al., proposing a full characterization of spectral-equipartite graphs. In this paper, we gave a characterization of disconnected spectral-equipartite graphs. Moreover, we introduced the concept eccentricity-equipartite graphs.